(untitled) (Research, Society and Development, 2020)
The objective of this research was to analyze the agreement between the degrees of risk attributed in the classification performed by the nurses, in relation to the protocol and between the classifiers. This is a descriptive study, conducted with the application of eleven clinical cases to thirty nurses in an Emergency Care Unit, based on the State Risk Classification Protocol-BA. The results showed moderate agreement, between classifiers and the protocol, according to the Kappa coefficient. Agreement between classifiers was also moderate, according to colorimetric density. The study found the importance of assessing the safety of risk classification protocols and pointed to the need to deepen the theme in question in health training schools in Brazil, in addition to adequate training for professionals to ensure the quality of care.